2016
DOI: 10.1183/23120541.00100-2015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients with adult-onset eosinophilic asthma

Abstract: Adult-onset eosinophilic asthma is increasingly recognised as a severe and difficult-to-treat subtype of asthma. In clinical practice, early recognition of patients with this asthma subtype is important because it may have treatment implications. Therefore, physicians need to know the distinct characteristics of this asthma phenotype. The objective of the present study was to determine the characteristic profile of patients with adult-onset eosinophilic asthma.130 patients with adult-onset (>18 years of age) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 34 publications
1
64
0
1
Order By: Relevance
“…10,39,40 However, these analyses were based on levels obtained at a single point in time and fail to take variability into account. 10,39,40 However, these analyses were based on levels obtained at a single point in time and fail to take variability into account.…”
Section: Discussionmentioning
confidence: 99%
“…10,39,40 However, these analyses were based on levels obtained at a single point in time and fail to take variability into account. 10,39,40 However, these analyses were based on levels obtained at a single point in time and fail to take variability into account.…”
Section: Discussionmentioning
confidence: 99%
“…Defined as ‘chronic changes in breathing pattern that result in dyspnoea and other symptoms, in the absence or in excess of the magnitude of physiological respiratory or cardiac disease’ [69], DB is observed in up to 52% of subjects with difficult asthma. DB seems to be most common in the obese and non-eosinophilic phenotypes of severe asthma [70,71]. Patients typically report very excessive dyspnea at relatively low levels of physical activity, that is dyspnea that is disproportionate with the objective level of asthma severity.…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…In these patients, the clinical profile may have added value. A recent study looking at the typical clinical profile of adult patients with eosinophilic asthma found that patients with this phenotype differed from patients with non-eosinophilic asthma with respect to a number of distinctive clinical features [72]. As compared to non-eosinophilic asthma patients, those with the eosinophilic phenotype had more often adult-onset asthma, were more often male, and had more often chronic rhinosinusitis with nasal polyposis.…”
Section: Added Value Of Clinical Features To Improve the Diagnosis Ofmentioning
confidence: 99%